2007
DOI: 10.1523/jneurosci.3789-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Damage Impairs Eye Contact During Conversations with Real People

Abstract: The role of the human amygdala in real social interactions remains essentially unknown, although studies in nonhuman primates and studies using photographs and video in humans have shown it to be critical for emotional processing and suggest its importance for social cognition. We show here that complete amygdala lesions result in a severe reduction in direct eye contact during conversations with real people, together with an abnormal increase in gaze to the mouth. These novel findings from real social interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
123
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 35 publications
16
123
0
2
Order By: Relevance
“…Support for amygdalar involvement in the lack of attention toward the eyes comes from elegant studies in patients with amygdala lesions. These patients showed reduced reflexive orientation toward the eyes when looking at faces on photographs or videos (Adolphs et al, 2005;Adolphs, 2007;Spezio et al, 2007). Thus, if reduced orientation to the eyes would be mediated by the amygdala in autism, this should be represented in decreased activity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Support for amygdalar involvement in the lack of attention toward the eyes comes from elegant studies in patients with amygdala lesions. These patients showed reduced reflexive orientation toward the eyes when looking at faces on photographs or videos (Adolphs et al, 2005;Adolphs, 2007;Spezio et al, 2007). Thus, if reduced orientation to the eyes would be mediated by the amygdala in autism, this should be represented in decreased activity.…”
Section: Discussionmentioning
confidence: 96%
“…Within normal functioning, an increase in amygdala activation seems to be associated with immediate orientation toward the eyes (Gamer and Büchel, 2009;Gamer et al, 2010). Along the same lines, patients with bilateral amygdala lesions fail to reflexively gaze toward the eyes (Spezio et al, 2007). Thus, if the amygdala triggers orientation toward salient social cues, such as the eyes, decreased amygdalar response to faces in ASD would rather support the reduced orientation hypothesis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…84 The latter finding has been shown at the single-neuron level in people with autism as well. Specifically, one study found groups of amygdalar neurons responsive to whole-face images both in people with autism and in controls.…”
Section: Social Deficitsmentioning
confidence: 76%
“…Further, these fixation durations predicted scores on a measure of social responsiveness (Speer et al, 2007). In the same vein, a recent study reported that more the eyes conveyed social information the more autistic subjects performed ocular saccades away from the eyes (Spezio, Huang, Castelli, & Adolphs, 2007), supporting the idea of an eye avoidance in autism (abnormality in eye contact, DSM IV). This is consistent with our findings that eyes were not well or realistically drawn by ASD children.…”
Section: Drawing Of Internal Facial Elements Eyes and Mouthmentioning
confidence: 80%